Redescription of the pupa of Mallochohelea termophila (Diptera: Ceratopogonidae) - Ronderos, María Marcela (2012)
The pupal exuvia of Mallochohelea termophila (Spinelli) is redescribed, photographed and illustrated mainly based on the type-series. Pupae of the type-series were collected with forceps from a thermal stream and were attached to rocks about 200 m from the spring head. Pupae from Uruguay were collected with a dipper in lotic and lentic environments. They were reared to adults in the laboratory. This is the first detailed pupal description of a species of Mallochohelea, and the first record of this species from Uruguay. Similarities and differences with the pupae of Neobezzia are provided.